2018
DOI: 10.3389/fphar.2018.00870
|View full text |Cite|
|
Sign up to set email alerts
|

The Reproductive Toxicity of Mequindox in a Two-Generation Study in Wistar Rats

Abstract: Mequindox (MEQ), belonging to quinoxaline-di-N-oxides (QdNOs), has been extensively used as a synthetic antibacterial agent. To evaluate the reproductive toxicity of MEQ, different concentrations of MEQ were administered to Wistar rats by feeding diets containing 0, 25, 55, 110, and 275 mg/kg, respectively. Each group consisting of 25 males and 25 females (F0) was treated with different concentrations of MEQ for 12-week period time, prior to mating and during mating, gestation, parturition and lactation. At we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Reproduction toxicity studies analyze the morphology and motility of male sperm, parturition, the number of live and dead pups, and the sex of the puppies. The same procedure is repeated to obtain the offspring of the second generation (Ganiger et al, 2007;Q. Liu et al, 2018;Montagnini et al, 2018;Wang et al, 2019).…”
Section: Other In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduction toxicity studies analyze the morphology and motility of male sperm, parturition, the number of live and dead pups, and the sex of the puppies. The same procedure is repeated to obtain the offspring of the second generation (Ganiger et al, 2007;Q. Liu et al, 2018;Montagnini et al, 2018;Wang et al, 2019).…”
Section: Other In Vivo Studiesmentioning
confidence: 99%
“…Reproduction toxicity studies analyze the morphology and motility of male sperm, parturition, the number of live and dead pups, and the sex of the puppies. The same procedure is repeated to obtain the offspring of the second generation (Ganiger et al, 2007; Q. Liu et al, 2018; Montagnini et al, 2018; Wang et al, 2019). Neurotoxicity studies evaluate neuropathological lesions and neurological dysfunctions (loss of memory, sensory defects, and learning and memory dysfunctions) after 28 or 90 days of administration (Ishtiaq et al, 2021; Xu et al, 2021).…”
Section: In Vivo Preclinical Studiesmentioning
confidence: 99%
“…44 Studies show that MEQ could induce reproductive toxicity and teratogenicity in rat maternal and embryonic populations. 45 Metabolites of MEQ exhibit toxicity that is more severe than that of the precursor. Five metabolites (M3, 3-hydroxymethyl 1-desoxymequindox; M6, bisdesoxymequindox; M7, 3-hydroxymethyl bisdesoxymequindox; M11, 2-isoethanol 4-desoxymequindox; and M14, 2-isoethanol bisdesoxymequindox) and one metabolite (M11) were observed in the rat liver and spleen, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Quinoxalines (Qx) are chemically synthesized antibacterial drugs that have a strong inhibitory effect on both gram-positive and gram-negative bacteria [ 1 , 2 ]. Due to the broad antimicrobial spectrum and obvious growth-promoting effects, Qx are used in excessive amounts by farmers as feed additives to obtain more economic benefits [ 3 ]. However, several studies have shown that Qx can cause toxic side effects such as trichothecation, photosensitivity, and adrenal cortical damage in livestock and poultry.…”
Section: Introductionmentioning
confidence: 99%